Learning by Doing : Working at Scale in Ethiopia - World Bank (Washington, DC, 2012)
In 2005, an estimated 15.2 million people or 80 percent of the total population of the Amhara Region in Ethiopia lived in rural areas where sanitation-related indicators were low. Open defecation was common; hand washing, particularly after defecation, was practiced infrequently; and general housing environments were unsanitary, with cohabitation with animals a common occurrence. There was a high prevalence of health issues correlating to poor sanitation and hygiene such as intestinal parasites, diarrhea, and eye and skin diseases. During that timeframe, the Water and Sanitation Program (WSP) worked with the Ministry of Health, providing support to design a Sanitation Strategy and On-Site Sanitation protocol. WSP also gained experience in scaling up sanitation by working closely with the Southern Nations, Nationalities, and People's Regional Government Health Bureau. These experiences and government motivation to change conditions provided an opportunity to design a community-led, systematic approach to implement a sustainable at-scale sanitation program based on the strategy and protocol.